sn-Glycerol-3-phosphate acyltransferases in plants - Chen, X.; Snyder, C.L.; Truksa, M.; Shah, S.; Weselake, R.J.
sn-Glycerol-3-phosphate acyltransferase (GPAT)catalyzes the acylation at sn-1 position of glycerol-3-phosphate to produce lysophosphatidic acid (LPA). LPA is an important intermediate for the formation of different types of acyl-lipids, such as extracellular lipid polyesters, storage and membrane lipids. Three types of GPAT have been found in plants, localizing to the plastid, endoplasmic reticulum and mitochondria. These GPATs are involved in several lipid biosynthetic pathways and play important biological roles in plant development. In the present review, we will focus on the recent progress in studying the physiological functions of GPATs and their metabolic roles in glycerolipid biosynthesis.
Keywords: GPAT; GLYCEROLIPID; LIPID POLYESTER; LIPID BIOSYNTHESIS; ARABIDOPSIS